Pattern of HIV-1 drug resistance among adults on ART in Nigeria (2013)
Background: The development of anitiretroviral drug resistance may limit the benefit of antiretroviral therapy. Therefore the need to closely monitor these mutations, especially the use of ART is increasing. This study was therefore designed to determine the ARV drug resistance pattern among ART na?ve and expose individuals attending a PEPFAR supported by antiretroviral clinic in Nigeria. Methodology: The study participants included patients attending the PEPFAR supported by University College Hospital (UCH), Ibadan ART clinic who have been on HIV treatment for at least one year with consecutive viral load of over 2000 copies/ml as well some ART Na?ve individuals with high (>50,000 copies/ml) baseline viral level attending the hospital for pre-ART assessment. Blood sample was collected from each individual for CD4 enumeration, viral load level determination and DNA sequencing for genotypic typing. Antiretroviral drug resistance mutations (DRM) were determined by using the Viroseq software and drug mutations generated by using a combination of Viroseq and Stanford algorithm. DRM were classified as major or minor mutations based on the June 2013 Stanford DR database. Results: The most common major NRTI, NNRTI and PI mutation were D67N (33.3%), Y181C (16.7%) and M46L/I (55.6%) respectively. Lamivudine (3TC) and emtricitabine (FTC); nevirapine (NVP) and nelfinavir (NFV) were the most common NRTI, NNRTI, and PI drugs to which the virus in the infected individuals developed resistance. Isolates from 4 patients were resistant to triple drug class, including at least one NRTI, NNRTI and a PI. Only one (4.8%) of the isolates from drug Na?ve individuals had major DRM that conferred resistance to any drug. Conclusion: Demonstration of high rates of antiretroviral DRM among patients on 1st and 2nd line ART and the presence of DRM in drug Na?ve individuals in this study show the importance of surveillance for resistance to ARV in line with the magnitude of scaling up of treatment program in the country.